A journey to remember: Malay traditional costume inspired / Muhammad Khalik Mustafa ... [et al.] - Mustafa, Muhammad Khalik; Sudarno, Noorain; Saleh, Nasyirah (2022)
A journey to remember is a fashion design collection that is inspired by traditional Ma-lay clothing. This adaptation is taken from vari-ous angles of wear, the way of wearing as well as the pieces of clothing that are changed through the resulting idea as a new design. The creation of this design work through the observation of the history of traditional Malay men's and wom-en's clothing. The history of the beginning of use in the Malay world expands from the concept to the changes of civilization through certain influ-ences such as trade, religion and technology. Old photos of Malay clothes are used as a reference in sketching new designs and also as a transfor-mation of new ideas in fashion design. From the process of carrying out the design through the method of drawing as well as up to 3D prototype will be the findings of the final study of a design